Preparation and characterization of chitosan/whey isolate protein active film containing TiO2 and white pepper essential oil - Wang, Ying; Wang, Ji; Lai, Jing; Zhang, Xin; Wang, Yongliang; Zhu, Yingchun (Frontiers in Nutrition, 2022)
Active packaging films are designed to improve quality and extend the food shelf life by incorporating functional active ingredients into biopolymer films. This study developed a bioactive film based on chitosan (CS) and whey isolated protein (WPI) incorporated with 0.01 wt% TiO2 and 0.1 wt% white pepper essential oil (WPEO). The physicochemical properties of the prepared film were also evaluated comprehensively. The results showed that water solubility and water vapor permeability of the film incorporated with TiO2 and WPEO were 25.09% and 0.0933 g mm m–2 h–1 KPa–1, respectively, which were significantly higher than those of other films (P < 0.05). In addition, the UV barrier properties of films incorporating TiO2 and WPEO have improved. The films were characterized by Fourier transform infrared (FTIR) and scanning electron microscopy (SEM). The FTIR results showed interactions between TiO2 and WPEO with CS/WPI compound, and the SEM results indicated a good incorporation of TiO2 into the composite films. The antioxidative and antibacterial properties of films were significantly enhanced by incorporating WPEO. According to results, the developed biocomposite film can be considered as a packaging material.